Prospective association between sleep duration and cognitive impairment: Findings from the China Health and Retirement Longitudinal Study (CHARLS) - Liu, Wenhua; Wu, Qingsong; Wang, Minghuan; Wang, Peng; Shen, Na (Frontiers in Medicine, 2022)
Objective: The association between sleep duration and cognition are inconclusive. Our study aimed to comprehensively investigate the effects of sleep duration on the risk of cognitive impairment in the middle-aged and older Chinese population. Methods: We used the longitudinal cohort data from waves 1 to 4 (2011 to 2018) of the China Health and Retirement Longitudinal Study (CHARLS). Self-reported exposures included total sleep duration, nocturnal sleep duration, post-lunch napping, and changes in sleep duration over time according to face-to-face interviews. Cognitive function was assessed by a Chinese version of the Modified Mini-Mental State Examination (MMSE). Results: A total of 7342 eligible participants were included. The mean age was 61.5 ± 6.5 years, and 48.9% (3588/7342) were male. We identified a U-shaped association of total sleep duration as well as nocturnal sleep duration with the risk of cognitive impairment. People with 7-8 hours of total sleep duration and 6-7 hours of nocturnal sleep had the lowest risk of cognitive impairment. Further results showed that post-lunch napping within two hours was beneficial to cognition and 60 minutes was optimal. Moreover, analyses of changes in sleep duration further supported that sleeping less or more was harmful to cognition. Notably, those “excessive-change” sleepers (from ≤ 6 to ≥ 9 hours, or from ≥ 9 to ≤ 6 hours) had more risks. Conclusions: Keeping 7-8 hours per day was related to the lowest risk of cognitive impairment in midlife and late life, and an optimal post-lunch napping was 60 minutes for these stable sleepers. Especially, excessive changes in sleep duration over time led to poorer cognition. Our work highlights the importance of optimal sleep habits to cognitive function. The self-reported sleep measures limited our findings, and further studies are needed for verification.